Pick up book machine - Muzahar, Nur Ain Shakira; Ismail, Adriana; Tarsik, Nor Famiza (Universiti Teknologi MARA, Kedah, 2017)
Pick up book machine is a model where it is designed to help and facilitate students that are having difficulties to pick up book which are placed on the top of the shelf in the library. We have done some research and found out that this problem can be overcome by designing this model. This machine can be use and when the power is running out, we can have recharged the battery which is more convenient and easy to use. In order to use this procedure, what the student need to do is, the student need to enter the serial number of the book and the pickup book machine will automatically pick up the book as instructed. This product also have sensor to detect the thickness of the book before grabbing the book. Besides, the machines also can be used to count the number of books that the student borrow on daily basis and the teacher can keep all data in their system. This product can detect popular book the student like to search and from there, this will help the management to add more addition to the most popular books for their collection in the library. Using machine or robot to assist users to get books in the library. In addition, this innovation will solve the problem of library staff for shelving purpose.